Non-Invasive Treatment of Reversible Caries Lesions in Vitro: A Novel Era in Denal Practice - Al-Obaidi, Rand; Alban Desoutter; Salehi, Hamideh; Cuisinier, Frederic; Jacquot, Bruno; Tassery, Herve (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2025)
Background: The efficacy of GC Tooth Mousse cream (CPP-ACP) as a remineralizing agent has been affirmed. Recently, nano-hydroxyapatite-containing dentifrice “KAREX” has been put on the market as a dental care product suitable for dental tissue renovation. Objective: Using an in vitro caries model to compare the remineralizing effect of the two products. Methods: 12 sound premolars were exposed to pH cycling model to induce subsurface lesions. Thereafter, teeth were randomly divided into 2 groups scanned by Raman microscopy two times: once after initial caries induction and once again after intervention to provide phosphate maps showing the net differences between affected and unaffected enamel areas. Each specimen was treated with the respective remineralizing agent for 5 min every 24 h for 21 days. The prominent phosphate peak at 960 cm–1 was nominated to observe changes in its intensity. Results: The width of the phosphate peak measured by FWHM was calculated across each spectral map to evaluate the effect of remineralizing agents on the crystalline structure of demineralized enamel. At the end of the treatment, a significant difference has been attained in respect to phosphate gain in the body of lesions treated by nHA-containing dentifrice compared to the counterpart treated by CPP-ACP. However, no significant differences were observed among the treatment groups with regard to enamel crystallinity. Conclusions: Enamel surface layer permeability along with material consistency might represent key factors in subsurface lesion remineralization.